Ten-year survival of women with breast cancer in the four major cities of Metro Manila - Mapua, Cynthia A.
This retrospective population-based cohort study determined the ten-year median survival time of the women with breast cancer in Manila, Quezon, Caloocan, and Pasay cities. The effects of age at diagnosis, socio-economic status (SES), histology, stage, and treatment on survival were likewise ascertained. It provided the Department of Health-Philippine Cancer Control Program (DOH-PCCP) baseline data for determining the earliness or laterness of diagnosis, the aggressiveness of the disease, and the effectiveness of medical treatment in the area.All breast cancer patients diagnosed in 1987 were followed-up for survival. Ascertainment of status was done ten years after diagnosis through home visits.There were 614 incident cases of breast cancer, of which four were males. Eighty-eight percent were histologically verified and 8.6were identified from death certificates. The histologically verified women had a mean age of 50.7 years (S.D. 12.9 years). Sixty-six percent were censored, of which majorities were lost to follow-up. Excluding those who were males, not histologically verified, and with saromas, 530 were left for the Kaplan-Meier estimation of median survival times, However, for cox regression analyses, those with unknown age, stage, treatment, and no follow-up periods were excluded, leaving 303 cases.The ten-year median survival time of the women with breast cancer in 1987 in Metro Manila was 60.33 months (95CI 38.51-74.84 months). Using Kaplan-Meier and Cox regression tests, SES, stage, and treatment were found to have significant associations with survival.Based on the findings of this study, it is recommended that increasing the knowledge of the public of the importance of early detection through breast self examination or health worker breast examination be the main thrust of DOH-PCCP. The public should be made aware that early detection and treatment, whether surgery alone or in combination with other therapies, would lead to longer survival.